2013
DOI: 10.1111/efp.12067
|View full text |Cite
|
Sign up to set email alerts
|

Characterization ofCorynelia uberataFr., a putative fungal pathogen ofPodocarpus falcatusinEthiopian forests

Abstract: Corynelia spp. are ascomycetes belonging to the order Coryneliales and are thought to be obligate parasites of trees in the Podocarpaceae. The aims of this study were to determine the disease intensity of Corynelia infection on Podocarpus falcatus in Ethiopian forests and verify the identity of Corynelia spp. from Ethiopia and other countries using morphological and molecular methods. Disease surveys were conducted in P. falcatus forest areas at Adaba-Dodola, Bushoftu, Menagesha, Shashamane and Wondo Genet in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 48 publications
(98 reference statements)
0
9
0
Order By: Relevance
“…Also, if mating patterns are mainly local and offspring therefore potentially inbred, seed dispersal may have a limited genetic rescue effect and therefore it remains unclear if birds reduce functional forest isolation at all. Overall, the evolutionary potential of the woody species in the church forests can be expected to be low, jeopardizing adaptation of the populations to emerging pests and diseases such as outbreaks of Corynelia, a fungal pathogen of Afrocarpus falcatus (Assefa et al 2014), or to changing environmental conditions such as climate change…”
Section: Field Survey Data Reveal High Floristic Variabilitymentioning
confidence: 99%
“…Also, if mating patterns are mainly local and offspring therefore potentially inbred, seed dispersal may have a limited genetic rescue effect and therefore it remains unclear if birds reduce functional forest isolation at all. Overall, the evolutionary potential of the woody species in the church forests can be expected to be low, jeopardizing adaptation of the populations to emerging pests and diseases such as outbreaks of Corynelia, a fungal pathogen of Afrocarpus falcatus (Assefa et al 2014), or to changing environmental conditions such as climate change…”
Section: Field Survey Data Reveal High Floristic Variabilitymentioning
confidence: 99%
“…An infected podo tree is a tree bearing visible fruiting bodies of C. uberata . Corynelia uberata was identified based on descriptions in earlier studies (Fitzpatrick, ; Benny et al ., ; Johnston & Minter, ; Minter, ; Assefa et al ., ). The climate description, altitude ranges and geographic locations of the study sites are indicated in Table .…”
Section: Methodsmentioning
confidence: 97%
“…The morphological and molecular identity of C. uberata in Ethiopia and related species elsewhere were recently described by Assefa et al . ().…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations